The Omni-Channel Profitability Paradox: Reconciling Volume Growth with Margin Preservation Through End-to-End Integrated Logistics - Akash Srivastava (International Journal of Intelligent Systems and Applications in Engineering, 2026)
The structural decoupling of revenue growth and operating margin in omnichannel retail represents a defining operational crisis of the modern digital economy. The cost architecture of the legacy retail network‚ comprised of fragmented fulfillment infrastructures‚ siloed inventory management systems‚ and misaligned departmental incentive structures‚ is fundamentally unsustainable at scale․ Modern consumer expectations dictate the use of a variety of fulfillment channels, including direct-to-consumer delivery, in-store pickup, and instant gratification windows․ The inefficiencies of a legacy retail infrastructure are compounded by systemic value leakage across the supply chain, from inbound procurement to reverse logistics processing․ This theoretical crisis is described as the breakdown of classical economies of scale in unit-level fulfillment and the illiquidity of inventory assets in a channel-partitioned order management system, the non-linear relationship with marginal picking and last-mile delivery variable costs as the volumes associated with digitally fulfilled orders rise. The Total Cost to Serve framework underlies each of these problems and provides the diagnostic and quantitative tools to identify the precise levels of e-commerce revenue at which negative marginal returns occur at the enterprise level․ End-to-end integrated logistics delivered as a digital visibility layer, an intelligence core of order management, and a micro-fulfillment infrastructure distributing physical assets close to the customer becomes the structural response to this paradox. Value, when the supply chain is abstracted or virtualized, becomes the substitutability of information for physical inventory․ Inventory repositioning, cash conversion, and circular reverse logistics are ways to transform the omnichannel supply chain from a burden of fragmentation into a platform for sustainable competitive advantage.